The Effect of Video Digital Stories on Students’ Listening Comprehension Achievement - Rendy Yudha Pradana (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This thesis examines the impact of video digital stories on the listening comprehension achievement of eighth-grade students at a junior high school in Probolinggo. Utilizing a quasi-experimental research design with a post-test-only control group, the study aimed to determine whether the implementation of video digital stories as learning material could significantly improve students' listening skills compared to conventional audio methods. Data were collected through listening comprehension tests, which included homogeneity tests (pre-test), try-out tests, and post-tests.
Repo 6 April 2026 Rudy K
Keywords: Digital Stories